Imidocarb Dipropionate Lacks Efficacy against Theileria haneyi and Fails to Consistently Clear Theileria equi in Horses Co-Infected with T. haneyi - Kelly Sears; Donald Knowles; Kelcey Dinkel; Philip W. Mshelia; Cynthia Onzere; Marta Silva; Lindsay Fry (Pathogens, 2020)
Control of Theileria equi, the primary cause of equine theileriosis, is largely reliant on acaracide use and chemosterilization with imidocarb dipropionate (ID). However, it is currently unknown if ID is effective against Theileria haneyi, the recently identified second causative agent of equine theileriosis, or if the drug maintains effectiveness against T. equi in the presence of T. haneyi co-infection. The purpose of this study was to address these questions using ID treatment of the following three groups of horses: (1) five T. haneyi infected horses; (2) three T. haneyi-T. equi infected horses; and (3) three T. equi-T. haneyi infected horses. Clearance was first evaluated using nPCR for each Theileria sp. on peripheral blood samples. ID failed to clear T. haneyi in all three groups of horses, and failed to clear T. equi in two of three horses in group two. For definitive confirmation of infection status, horses in groups two and three underwent splenectomy post-treatment. The T. equi-nPCR-positive horses in group two developed severe clinical signs and were euthanized. Remaining horses exhibited moderate signs consistent with T. haneyi. Our results demonstrate that ID therapy lacks efficacy against T. haneyi, and T. haneyi-T. equi co-infection may interfere with ID clearance of T. equi.